Economic impact of maritime piracy on Artisanal fishermen in Somalia - Jama, Ahmed Khadar Abdi; Ariffin, Muhammad Irwan; Abdullah Yusof, Selamah (2021)
This study aims to examine the economic impacts of maritime piracy on artisanal fishermen in Somalia. A survey questionnaire was administered to a sample of 282 fishermen that are selected through systematic sampling. The study found that a significant number of Somali fishermen are passive in their response to piracy attacks and do not feel threatened by it. As a result, Somali fishermen do not adopt commonly adopted strategies such as hiring security guards, or reducing the boat or cargo value that are taken by foreign fishermen. Result also suggests that piracy in Somalia has no economic consequences to fishermen; it does not affect their fish catch, income from fishing, price of fish catch, cost of fishing, investment in fishing, crew members, fish supply, and fishing efforts.